Bone Marrow Aspirate Concentrate Does Not Improve Osseous Integration of Osteochondral Allografts for the Treatment of Chondral Defects in the Knee at 6 and 12 Months: A Comparative Magnetic Resonance Imaging Analysis. Issue 2 (February 2019) - Wang, Dean; Lin, Kenneth M.; Burge, Alissa J.; Balazs, George C.; Williams, Riley J.
Background: Poor osseous integration after fresh osteochondral allograft transplantation (OCA) may be associated with graft subsidence and subchondral bone collapse after implantation. The augmentation of OCA with bone marrow aspirate concentrate (BMAC) has been hypothesized to improve osseous incorporation of the implanted allograft. Purpose: To evaluate the effect of autogenous BMAC treatment on osseous integration at the graft-host bony interface after OCA. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review of patients treated with OCA+BMAC or OCA alone for full-thickness chondral defects of the distal femur from March 2015 to December 2016 was conducted. Seventeen knees treated with OCA+BMAC and 16 knees treated with OCA alone underwent magnetic resonance imaging (MRI) in the early postoperative phase (mean, 6 months). Eighteen knees treated with OCA+BMAC and 16 knees treated with OCA alone underwent MRI in the late postoperative phase (mean, 12 months). Bone, cartilage, and ancillary features on MRI were graded using the Osteochondral Allograft MRI Scoring System (OCAMRISS) by a musculoskeletal radiologist blinded to the patient's history and treatment. Results: There were no significant differences in the demographics or lesion characteristics between treatment groups in either postoperative phase. In the early postoperative phase, the mean OCAMRISS bone score was 3.0 ± 0.7 and 3.3 ± 0.7 for the OCA+BMAC group and OCA alone group, respectively ( P = .76); 71% (OCA+BMAC) and 81% (OCA alone) of MRI scans demonstrated discernible clefts at the graft-host junction ( P = .69), and 41% (OCA+BMAC) and 25% (OCA alone) of MRI scans demonstrated cystic changes at the graft and graft-host junction ( P = .46). In the late postoperative phase, the mean OCAMRISS bone score was 2.7 ± 0.8 and 2.9 ± 0.8 for the OCA+BMAC group and OCA alone group, respectively ( P = .97); 44% (OCA+BMAC) and 63% (OCA alone) of MRI scans demonstrated discernible clefts at the graft-host junction ( P = .33), and 50% (OCA+BMAC) and 31% (OCA alone) of MRI scans demonstrated the presence of cystic changes at the graft and graft-host junction ( P = .32). The mean OCAMRISS cartilage, ancillary, and total scores were not significantly different between groups in either postoperative phase. Conclusion: OCA augmented with BMAC was not associated with improved osseous integration; decreased cystic changes; or other bone, cartilage, and ancillary feature changes compared with OCA alone.